Bank Specific Risks and Financial Stability Nexus: Evidence From Pakistan - Chai, Zhengmeng; Sadiq, Muhammad Nauman; Ali, Najabat; Malik, Muhammad; Hamid, Syed Ali Raza (Frontiers in Psychology, 2022)
This article investigates the nexus between bank-specific risks and the financial stability of the banks for a panel data set of 15 scheduled banks in Pakistan over a 12-year period from 2009 to 2020. Using the fixed-effect model, the study result shows that bank-specific risks, i.e., credit risk and liquidity risk are detrimental to bank stability, whereas funding risk has no significant impact on bank stability. Besides these, bank size has also a negative impact on bank stability, whereas the return on assets (ROA) revealed a positive influence. To ensure stability, bank management should establish policies that confirm secure loan granting and timely reimbursement from customers to minimize the credit risk. Besides this, management should keenly observe the liquidity position and should also effectively mobilize the customer deposits to attain financial stability.